CO2 conversion to volatile fatty acids by anaerobic granular sludge and Mg0 - Samanides, Charis G.; Vyrides, Ioannis (My University, 2023)
Platform chemicals (VFAs) production through CO2 utilization technologies plays a crucial role in international efforts for climate change mitigation. In this study, a new approach for sustainable and eco-friendly CO2 bioconversion to acetic acid proposed using 4 g L−1 magnesium ribbon (Mg0) in-situ and homoacetogen-enriched anaerobic granular sludge. To suppress methanogenesis three inhibition strategies were investigated. The use of NaCl (50, 70, 90 g L−1), 2-bromoethanesulfonate (4 mM BES), and a short heat-shock pre-treatment were applied to anaerobic granular sludge. The most effective strategy for methanogenesis inhibition and acetic acid production was the thermal treatment producing 2023,07 mg L−1 of acetic acid after 32 days (Cycle 7) with a maximum production rate of 234,58 mg L−1 day−1 at cycle 3 (after 14 days). Following the system with BES producing 1369,45 mg L−1 of acetic acid with a maximum production rate of 111,76 mg L−1 day−1 at cycle 3. The systems exposed to NaCl generated fewer VFAs compared to the other two systems (BES, Heat-shock). After the third cycle and until the end of the experiment (cycle 7), at the two systems (BES, Heat-shock), the acetic acid production rate slightly increased, whereas the methane significantly increased. At the end of cycle 7, the hydrogenotrophic methanogens Methanolinea was found in a high relative abundance and hydrogenotrophic methanogens acted antagonistically towards homoacetogens.
Keywords: Anaerobic granular sludge; CO2 utilization; Homoacetogens; Magnesium ribbon; Methanogen inhibition; Volatile fatty acids